Bacteremia in the red blood cells obtained from the cell saver in patients submitted to heart surgery - Manuel Luque-Oliveros (Universidade de São Paulo, 2020)
Objective: to determine the microbiological characteristics of the red blood cells obtained with the cell saver in heart surgery patients on an extra-body circuit. Method: a cross-sectional and descriptive study conducted with 358 patients scheduled for heart surgery where the saver was used. Sociodemographic variables were collected, as well as from the saver and of the microbial identification in the re-infusion bag proceeding from the cell saver. Informed consent performed. Results: of the 170 GRAM+ bacteria isolations, the most frequent species were Staphylococcus epidermidis in 69% (n=138) of the cases and Streptococcus sanguinis with a report of 10% (n=20). Significant differences were found in the Staphylococcus epidermidis strain in patients with a Body Mass Index ≥25 (p=0.002) submitted to valve surgery (p=0.001). Vancomycin was the antimicrobial which resisted the Staphylococcus epidermidis strain with a minimum inhibitory concentration of >16 µg/ml. Conclusion: the microbiological characteristics of the red blood cells obtained after processing autologic blood recovered with the cell saver during heart surgery are of GRAM+ bacterial origin, the most isolated species being Staphylococcus epidermidis. Consequently, in order to reduce the presence of these GRAM+ cocci, an antibiotic should be added to the cell saver reservoir, according to a previously established protocol.